2003
DOI: 10.1016/s1097-2765(03)00446-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of mRNAs Regulated by the Nonsense-Mediated and 5′ to 3′ mRNA Decay Pathways in Yeast

Abstract: Transcripts regulated by the yeast nonsense-mediated and 5' to 3' mRNA decay pathways were identified by expression profiling of wild-type, upf1Delta, nmd2Delta, upf3Delta, dcp1Delta, and xrn1Delta cells. This analysis revealed that inactivation of Upf1p, Nmd2p, or Upf3p has identical effects on global RNA accumulation; inactivation of Dcp1p or Xrn1p exhibits both common and unique effects on global RNA accumulation but causes upregulation of only a small fraction of transcripts; and the majority of transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
391
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(431 citation statements)
references
References 45 publications
29
391
1
1
Order By: Relevance
“…As in yeast 8 , we observed upregulation of numerous transposonderived RNAs and transcripts containing uORFs in NMD-deficient mammalian cells, indicating that these are conserved classes of NMDregulated transcripts. The other classes of NMD substrates in yeast were not identified in our analyses (e.g., pseudogene and polycistronic transcripts; and transcripts with inefficient pre-mRNA splicing, leaky scanning or +1 frameshifting); this absence probably reflects the limited composition of current mammalian microarrays and incomplete annotation of the human genome.…”
Section: E T T E R Ssupporting
confidence: 65%
See 1 more Smart Citation
“…As in yeast 8 , we observed upregulation of numerous transposonderived RNAs and transcripts containing uORFs in NMD-deficient mammalian cells, indicating that these are conserved classes of NMDregulated transcripts. The other classes of NMD substrates in yeast were not identified in our analyses (e.g., pseudogene and polycistronic transcripts; and transcripts with inefficient pre-mRNA splicing, leaky scanning or +1 frameshifting); this absence probably reflects the limited composition of current mammalian microarrays and incomplete annotation of the human genome.…”
Section: E T T E R Ssupporting
confidence: 65%
“…In contrast to the upregulated transcripts, the seven downregulated transcripts that we tested either showed no change in steady-state abundance or stability on depletion of Rent1 or showed no concordant changes on depletion of Rent2, as assessed by northern blotting (data not shown). Thus, as in yeast 8 , we conclude that few, if any, mammalian transcripts that showed decreased abundance by microarray analysis are regulated by NMD.…”
Section: E T T E R Ssupporting
confidence: 65%
“…Ssu Ϫ mutations, by contrast, would exacerbate the effect of poor context, increase leaky scanning of the first AUG codon and intensify the effect of NMD in lowering SUI1 mRNA abundance. At odds with this possibility, however, He et al reported that SUI1 mRNA abundance is not altered by inactivation of NMD in different upf mutants (18). Thus, in view of previous findings that mRNA stability is coupled to translational efficiency in yeast (25,43), the simplest interpretation of our findings seems to be that the changes in translational efficiency produced by the eIF mutations under study lead indirectly to alterations in mRNA degradation by a non-NMD mechanism.…”
contrasting
confidence: 48%
“…8A). Importantly, these differences in expression are nearly eliminated by Sui Ϫ mutations in eIF1 (K60E), eIF2␤ (SUI3-2), and eIF1A (SE), while the difference in expression between SUI1-UUU -lacZ and SUI1-opt-lacZ is exacerbated by the Ssu Ϫ mutations affecting eIF1 (E48V) and eIF1A (17)(18)(19)(20)(21) (Fig. 8).…”
Section: Vol 31 2011 Multiple Eifs Mediate Aug Context Effects 4821mentioning
confidence: 99%
See 1 more Smart Citation